Computational and Experimental Study of High-Performance Lubricants in Extreme Environments - Keffer, David J.; Edwards, Brian J.; Adcock, Jamie; Steele, Bill; Gresham, Jennifer (2008)
The intelligent design of lubricants that perform under extreme environments, such as arctic or space conditions, requires an understanding of the how the tribological properties are related to the molecular structure of the lubricant. The purpose of this grant was to understand the relationship between molecular-level perfluoropolyether (PFPE) lubricant architecture and its resulting properties of tribological relevance, including rheological properties and chemical stability. We synthesized a series of PFPE lubricants varying key architectural elements. We characterized the rheological properties of the experimentally synthesized lubricants. We performed non-equilibrium molecular dynamics (NEMD) simulation to model the rheological properties and to understand the fundamental mechanisms governing the relationship between molecular structure and viscosity. We furthermore performed a multiscale suite of simulations combining quantum mechanical (QM) calculations of the reaction rate constants and reactive molecular dynamics (RMD) to model the chemical stability of the components as a function of architecture.